(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The achievements of modern medicine are largely based on the successes of physics, technology and medical instrumentation. The nature of the disease and the mechanism of healing are in many cases explained on the basis of biophysical concepts.